Cognitive dissonance in dealing with plagiarism in academic writing - Law, Lily; Ting, Su Hie; Jerome, Collin (Elsevier Ltd., 2013)
The study examined university students’ plagiarism in completing written assignments. The specific aspects studied were frequency of citation and help-seeking strategies, attitudes towards penalties for plagiarism and rationalisations for omission of citations. Questionnaires were distributed at the beginning and end of an Academic Reading and Writing course at a Malaysian public university. The analysis of 169 pre- and 126 post-questionnaires indicate that after formal instruction on citation conventions, self-reports of appropriate citation and help-seeking strategies for assignment completion increased. There were no significant changes in self-reports of unethical help-seeking strategies but the respondents reported significantly less use of some unethical citation strategies. Surprisingly, at the end of the semester, fewer students agreed that students caught for plagiarism should fail the assignment, possibly due to heightened awareness of their own assignment completion strategies which run into plagiarism. In the post-questionnaire, fewer respondents justified omission of citations on the grounds of lack of knowledge and non-deduction of marks for omitting citations in assignments. With an increase in appropriate assignment completion strategies and a concomitant decrease in inappropriate strategies, there is a lessened need to resolve the cognitive dissonance arising from inconsistency between maintaining a moral self-image and committing academic misconduct.